The congregation and church of England? William Tyndale’s approach to lexical and ecclesiological reform between 1525 and 1535 - Martin, Jan James (2022)
As one of the earliest English religious reformers of the 1520s, William Tyndale sought to influence ecclesiological reform in England through a vernacular printing campaign. Beginning with an Engl..., En tant qu’un des premiers réformateurs anglais des années 1520, William Tyndale chercha à influencer la réforme ecclésiologique en Angleterre par une campagne d’écrits en langue vernaculaire. Comm...
Keywords: English Bible translation; Thomas More; William Tyndale; Church; Congregation; congrégation; ecclesiological reform; traduction anglaise de la Bible; église réforme ecclésiologique